- - Porta i Sales, Josep (Acta Bioethica, 2000)
It is described the frame for applying palliative care to the different problems encountered by patients and their families at the end of life. Sedation is a therapeutic manoeuvre frequently used in palliative medicine, that could eventually infringe some ethical principles. From our standpoint, beneficence and autonomy are probably the most affected principles when sedation is considered. Some measures to prevent such violations to occur are discussed, and suggestions intended to guide in decisionmaking are proposed.